2018
DOI: 10.1038/s41598-018-22035-z
|View full text |Cite
|
Sign up to set email alerts
|

Improving RNAi in the Brown Marmorated Stink Bug: Identification of target genes and reference genes for RT-qPCR

Abstract: The brown marmorated stink bug (BMSB) is native to Asia and recently invaded the USA. RNA interference (RNAi) is a gene silencing mechanism in which the introduction of double-stranded RNA (dsRNA) inhibits gene function by degrading target mRNA. In dsRNA stability assays, the dsRNases present in the hemolymph and salivary gland secretions of BMSB showed lower activity than those in the hemolymph of Heliothis virescens. We evaluated six housekeeping genes (18S rRNA, EF1-α, Actin, Ubiquitin, 60S RP and β-Tubulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 42 publications
3
60
0
4
Order By: Relevance
“…29,30 In addition, we found that Snf7 dsRNA was the most lethal among the dsRNAs tested. This result is in agreement with a number of studies that have shown high mortality in several insect species exposed to Snf7 dsRNA, including Diabrotica virgifera virgifera, 36 Diabrotica undecimpunctata howardi, 37 Halyomorpha halys 38 and Amrasca biguttula biguttula. 39 Interestingly, ingestion of V-ATPase A dsRNA induced the highest level of gene knockdown at day 10 (75.6%), although no significant mortality of the weevils was observed.…”
Section: Discussionsupporting
confidence: 92%
“…29,30 In addition, we found that Snf7 dsRNA was the most lethal among the dsRNAs tested. This result is in agreement with a number of studies that have shown high mortality in several insect species exposed to Snf7 dsRNA, including Diabrotica virgifera virgifera, 36 Diabrotica undecimpunctata howardi, 37 Halyomorpha halys 38 and Amrasca biguttula biguttula. 39 Interestingly, ingestion of V-ATPase A dsRNA induced the highest level of gene knockdown at day 10 (75.6%), although no significant mortality of the weevils was observed.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to the control larvae, the mean expression level of diap1, v-ATPase A and v-ATPase E in the f-RNAi treated larvae reduced to 50.2, 3.6, 3.4%, respectively. The knockdown effect of diap1 f-RNAi seems to be lower than that of v-ATPase genes, although, the reduced rate of diap1 mRNA level is nearly equivalent to that in previous diap1 f-RNAi studies 14,20,22,25 showing the obvious phenotype. Considering these facts, we determined that our knockdown effect of diap1 is reasonable.…”
Section: Resultssupporting
confidence: 50%
“…For these reasons, diap1 is one of the candidate target gene for RNAi pesticides and has been investigated in various pests. So far, RNAi of the diap1 gene by injecting the dsRNA into the hemocoel of pest has been shown to induce over 70% mortality in T. castaneum (Coleoptera) 14 , Anoplophora glabripennis (Coleoptera) 20 , Musca domestica (Diptera) 21 , Delia radicum (Diptera) 21 , Heliothis virescens (Lepidoptera) 22 , Lygus lineolaris (Hemiptera) 23 and Apolygus lucorum (Hemiptera) 24 . Diap1 silencing by f-RNAi has also been reported to induce 30– 78% of mortality in Agrilus planipennis 24 , T. castaneum 14 , and Diaphorina citri 25 .…”
Section: Introductionmentioning
confidence: 99%
“…For a role in crop protection, oral uptake of dsRNA and subsequent efficient uptake in the gut have to be evaluated . Supplying dsRNA in artificial diet resulted in the knockdown of targeted genes in different species of Hemiptera including the small brown planthopper, Laodelphax striatellus (Fallén), the brown planthopper, Nilaparvata lugens (Stål), the corn planthopper, Peregrinus maidis (Ashmead), the white‐backed planthopper, Sogatella furcifera (Horvath), the kissing bug, Rhodnius prolixus (Stål), the pea aphid, Acyrthosiphon pisum (Harris), the wheat aphid, Sitobion avenae (Fabricius), the potato/tomato psyllid, Bactericera cockerelli (Sulc), the Asian citrus psyllid, Diaphorina citri (Kuwayama), the brown marmorated stink bug, Halyomorpha halys (Stål) and the tobacco whitefly, Bemisia tabaci (Gennadius) . However, oral delivery in some hemipteran pests, such as the tarnished plant bug Lygus lineolaris (Palisot de Beauvois) and the pea aphid A. pisum , is confounded by high ribonuclease activity in the saliva which degrades the dsRNA .…”
Section: Introductionmentioning
confidence: 99%